Pioneer church - Otto, Carolyn (Henry Holt, 1999)
In the mid-1700s, four families build a log church on a hill in central Pennsylvania, and congregations worship in it and its replacement up through World War II. Based on the history of Old Zion church in Brickerville, Pennsylvania.